2016
DOI: 10.1089/jmf.2015.0124
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation with a Low Dose of Polyphenol-Rich Grape Pomace Extract Prevents Dextran Sulfate Sodium-Induced Colitis in Rats

Abstract: Evidence from several epidemiological and experimental studies points to a beneficial role of dietary polyphenols in inflammatory bowel disease. In this study, we investigate the protective effect of dietary supplementation with various amounts of a polyphenol-rich grape pomace extract (GPE) on the development of dextran sulfate sodium (DSS)-induced colitis in rats. Rats were fed 21 days on a semisynthetic diet enriched with GPE (0.1%, 0.5%, and 1%), and acute colitis was induced by DSS (40 g/L in the drinking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
1
12
0
1
Order By: Relevance
“…In Figure 1 , considerable decelerations in weight gain at those points in the experiment can be observed, especially in the rats from the feed and control sausage cohorts. A possible explanation for this apparent protection against AOM and/or DSS inflammation in the case of the functional sausage cohort may be the known anti-inflammatory effect of anthocyanins [ 19 , 20 , 21 , 22 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Figure 1 , considerable decelerations in weight gain at those points in the experiment can be observed, especially in the rats from the feed and control sausage cohorts. A possible explanation for this apparent protection against AOM and/or DSS inflammation in the case of the functional sausage cohort may be the known anti-inflammatory effect of anthocyanins [ 19 , 20 , 21 , 22 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the animal models used in the 14 included in vivo animal studies: Wistar rats (n ¼ 4) [31,34,36,40], C57BL/10 SnSn mice (n ¼ 1) [35], C57BL/6J mice (n ¼ 1) [37], both C57BL/6 and IL-deficient mice (n ¼ 1) [38], both C57BL/6 and CD1 mice (n ¼ 1) [41], C57BL/6 mice alone (n ¼ 1) [43], weaned pigs (n ¼ 2) [33,44], SpragueeDawley rats (n ¼ 1) [32], IL-10 deficient mice (n ¼ 1) [39], and BALB/C mice (n ¼ 1) [45]. The current animal models used to assess intestinal inflammation are summarized in Table 1.…”
Section: Literature Search Study Selection and Characteristicsmentioning
confidence: 99%
“…In in vivo animal studies, resveratrol as an extract was the most commonly used source of PCs (n ¼ 6) [31,32,34,35,44,45]; after its oral (n ¼ 5) [31,34,35,44,45], or intravenous administration (n ¼ 1) [32]. Other PC sources used in in vivo animal studies were: oral grape seed extract (GSE) (n ¼ 2) [38,39], oral grape pomace extract (n ¼ 1) [40], oral cranberry extract (n ¼ 1) [37], oral curcumin (n ¼ 1) [35], oral hesperidin (n ¼ 1) [43], oral Olive (Olea europaea) leaves extract (n ¼ 1) [41], genistein by intestinal injection (n ¼ 1) [36], and oral chlorogenic acid (n ¼ 1) [33]. Complete information on the included animal studies is reported in Table 2.…”
Section: Literature Search Study Selection and Characteristicsmentioning
confidence: 99%
“…En algunos de estos sub-productos también están presentes taninos, vitaminas, carotenos, pigmentos y otros. En los últimos años se han publicado diversos estudios que señalan que los compuestos bioactivos naturales extraídos de los vegetales son beneficiosos para la salud humana ya que poseen actividad antioxidante, tienen propiedades anticancerígenas, cardioprotectoras, antimicrobianas y antiinflamatorias 10,23,32,33 . Por esto la extracción de este tipo de compuesto en conjunto con el concepto de economía circular, es un "hot topic" en la actualidad.…”
Section: Desarrollo 1 Sub-productos Agroindustriales Vegetalesunclassified